Non-concentric single-mode optical fiber dispersion - Doni Basdyo; Yoli Zairmi; Preecha Yupapin (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2022)
The application of wave transmission in telecommunication optical fiber still has problems in the form of dispersion. For this reason, it is necessary to design and operate optical fiber dispersion that is shifted or not concentric with simulation as the first step in designing which is easier, cheaper and has a high level of accuracy. The purpose of this study was to analyze the design and operation of the displaced optical fiber dispersion and determine the wavelength value at the minimum dispersion value using OptiFiber software. The input parameters consist of the refractive index of the optical fiber in the range of 1.4615 to 1.44692 and the wavelength range of 1.4 µm to 1.5 µm. The dispersion result obtained is a minimum wavelength of 1.5506 µm. This result is close to the theoretical value of 1.55 µm with attenuation and dispersion at one wavelength point. The results of this study can be used for validation in experiments.